Anti-Tumour Promoting Activity of Selected Malaysian Vegetables and Fruits, and Identification of Anti-Tumour Promoting and Antioxidant Compounds from Coleus Tuberosus, Benth (Ubi Kemili) - Lim, Yang Mooi (2002)
A convenient short-term in vitro assay, the inhibition of Epstein-Barr virus (EBV) activation induced by phorbol 12-myristate 13-acetate (PMA) and sodium n- butyrate was conducted to detect the naturally occurring anti-tumour promoters of 133 vegetables and fruits. Forty-two plants showed strong inhibitory activity, 33 plants showed moderate inhibitory activity, 21 plants were found to be weakly active and 37 plants were inactive. Coleus tuberosus, Benth was chosen for further study because it showed the strongest activity. Phytosterols (CT 1) and 2a,3p.dihydroxyl-12-oleanen-28-oic-acid (CT 2) were isolated from Coleus tuberosus, Benth based on bioassay-guided fractionation. CT 1 was identified as a mixture consisting of stigmasterol (32.0%), campesterol (27.7%) and β-sitosterol (40.3%) by gas chromatography. CT 2 was established as 2a,3p.dihydroxy- 12-oleanen-28-oic acid Five plants that showed the highest anti-tumour promoting activity namely, Carica papaya, Ba"ingtonia macrostachya, Coleus tuberosus, Mangifera indica and Eugenia polyantha also exhibited strong antioxidant activity compared to a- tocopherol in the ferric thiocyanate (FTC) method and showed more than 60% inhibition rate in the xantbinelxanthine oxidase system. Those plants mentioned above did not exhibit any activity in scavenging stable DPPH (1,1-diphenyl-2- picrylbydrazyl) radicals and hydrogen peroxide stim.. in differentiated HL 60 cells by PMA. Isolated compounds CT 1 and CT 2 and commercial standards campesterol, stigmasterol, and ,β-sitosterol were also tested for their antioxidant activity. Campesterol, CT I, stigmasterol, and ,β-sitosterol demonstrated more than 50010 inhibition rate in scavenging superoxide anion induced in the xanthine/xanthine oxidase system. CT 2 showed an inhibition rate of 46.62%. Campesterol, CT 1 and ,β-sitosterol showed more than 50% inhibition rate at 2 µg/ml in scavenging hydrogen peroxide induced in differentiated Hl. 60 cells, but CT 2 and stigmasterol, attained an inhibition rate of only 32.97% and 16.37%, respectively. All compounds did not exhibit any activity in scavenging stable DPPH radicals. Campesterol, CT 1, CT 2, stigmasterol and ,β-sitosterol were found to have very strong anti-tumour promoting activity and their ICso were determined as 2 µg/ml, 0.7 µg/ml, 0.1 µg/ml, 0.6 µg/ml and 1 µg/ml, respectively. The optimum combination effect of stigmasterol, P.sitosterol and campesterol towards the anti-tumour promoting activity was obtained at 40 µg/ml of each compound analysed by the response surface methodology (RSM). Campesterol was assessed to cause a negative interaction to p sitosterol, while, stigmasterol caused a negative interaction to campesterol at concentrations higher than 20 µg/ml. Immunoblotting analysis was used as a confirmation test for the detection of the EBV early antigen EA-D and EA-R EA-D was detected as a darker band of about 50-52 kDa while EA-R showed up as a fade band of about 85 kDa. In conclusion, CT 1 and CT 2 were found to show strong anti-tumour promoting activity. This supports the assumption that the consumption of vegetables and fruits is a highly recommended strategy for cancer chemoprevention and can be a practical approach to control cancer.